KEDUDUKAN PEREMPUAN DALAM SISTEM POLITIK PERSPEKTIF ULAMA KONTEMPORER - Nabila, Inatsa Zulfa; Maksum, Muh Nur Rochim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The current reality is that the role of women is not given more attention so that society does not realize the importance of women's participation in the political system. Women are always considered weak when it comes to their physical appearance, moreover, the nature that has been assigned to women is often seen as an obstacle for them to serve in the government system. On the other hand, Islam's view of women does not differentiate their position. Islam does not recognize discrimination between women and men. However, the majority of fiqh scholars who follow the Manhaj Salaf agree to prohibit women from becoming leaders. The aim of this research is to describe the position of women in the political system according to several contemporary scholars, including Yusuf Al-Qardhawi, Quraish Shihab, and Hasan Al-Banna. The paradigm of this research is qualitative research. Using this type of library research. The object of study in this research is the thinking of contemporary ulama regarding the law for women in politics. This research describes the various views of the three scholars along with the basis used in deciding the legal position of women in politics